The importance of rare species: a trait‐based assessment of rare species contributions to functional diversity and possible ecosystem function in tall‐grass prairies. Issue 1 (12th December 2013) - Jain, Meha; Flynn, Dan F.B.; Prager, Case M.; Hart, Georgia M.; DeVan, Caroline M.; Ahrestani, Farshid S.; Palmer, Matthew I.; Bunker, Daniel E.; Knops, Johannes M.H.; Jouseau, Claire F.; Naeem, Shahid
Abstract The majority of species in ecosystems are rare, but the ecosystem consequences of losing rare species are poorly known. To understand how rare species may influence ecosystem functioning, this study quantifies the contribution of species based on their relative level of rarity to community functional diversity using a trait‐based approach. Given that rarity can be defined in several different ways, we use four different definitions of rarity: abundance (mean and maximum), geographic range, and habitat specificity. We find that rarer species contribute to functional diversity when rarity is defined by maximum abundance, geographic range, and habitat specificity. However, rarer species are functionally redundant when rarity is defined by mean abundance. Furthermore, when using abundance‐weighted analyses, we find that rare species typically contribute significantly less to functional diversity than common species due to their low abundances. These results suggest that rare species have the potential to play an important role in ecosystem functioning, either by offering novel contributions to functional diversity or via functional redundancy depending on how rare species are defined. Yet, these contributions are likely to be greatest if the abundance of rare species increases due to environmental change. We argue that given the paucity of data on rare species, understanding the contribution of rare species to community functional diversity is an important first step to understanding the potential role of rare species in ecosystem functioning.